BACKPACKER TEACHING DAN MERDEKA BELAJAR DI UJUNG KULON, BANTEN - Imam Muhtadin (Media Resonansi Pengabdian Masyarakat, 2025)
Education in remote areas faces numerous challenges, including limited access to qualified teachers and inadequate learning resources. One innovative approach to addressing these challenges is the Backpacker Teaching program, which promotes flexible and experiential learning. This program was implemented in the Backpacker Teaching and Merdeka Belajar in Ujung Kulon, Banten initiative, conducted from December 21 to 31, 2024. The program aimed to enhance students’ motivation and learning quality through creative methods such as Canva for digital literacy, computer-based report writing and narrative development, participatory teaching techniques, active learning, educational games, and achievement motivation training.The implementation of this program emphasized technology-based learning, active student engagement, and enjoyable educational experiences to facilitate better comprehension. The results indicate significant improvements in students' digital literacy, creativity, confidence in public speaking, and active participation in learning. Furthermore, local teachers gained insights into alternative teaching methods that can be incorporated into daily classroom practices. The findings suggest that Backpacker Teaching can serve as an effective educational model to support the Merdeka Belajar policy, particularly in remote regions. Therefore, similar programs should be further developed with enhanced technological support, teacher capacity-building initiatives, and collaboration with various stakeholders to ensure sustainability and long-term impact.Keywords : Backpacker Teaching, Merdeka Belajar, remote education, digital literacy, innovative teaching methods